![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,\frac{2}{3}+\frac{4}{9}+\frac{1}{5}+\frac{2}{15}+\frac{3}{2}-\frac{17}{18}\)
\(< =>\frac{4}{9}+\frac{3}{2}+\left(\frac{2}{3}+\frac{1}{5}+\frac{2}{15}\right)-\frac{17}{18}\)
\(< =>\frac{8}{18}+\frac{27}{18}+\left(\frac{10}{15}+\frac{3}{15}+\frac{2}{15}\right)-\frac{17}{18}\)
\(< =>\frac{35}{18}+1-\frac{17}{18}\)
\(< =>\frac{53}{18}-\frac{17}{18}\)
\(< =>2\)
\(2,\frac{13}{28}\cdot\frac{5}{12}-\frac{5}{28}\cdot\frac{1}{12}\)
\(< =>\left(\frac{13}{28}-\frac{5}{28}\right)\cdot\left(\frac{5}{12}-\frac{1}{12}\right)\)
\(< =>\frac{2}{7}\cdot\frac{1}{3}\)
\(< =>\frac{2}{21}\)
\(3,\frac{19}{4}\cdot\frac{15}{23}-\frac{15}{4}\cdot\frac{7}{23}+\frac{15}{4}\cdot\frac{11}{23}\)
\(< =>\frac{285}{92}-\frac{105}{92}+\frac{165}{92}\)
\(< =>\frac{15}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
bài 1
a) 155 - 10.(x+1) = 55
=>10 .(x+1) = 100
=>x + 1 = 10
=>x = 9
còn lại tương tự
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{8}{9}\) : ( 2 - 3 \(\times\) y) = \(\dfrac{5}{3}\)
2 - 3 \(\times\) y = \(\dfrac{8}{9}\) : \(\dfrac{5}{3}\)
2 - 3 \(\times\) y = \(\dfrac{8}{15}\)
3 \(\times\) y = 2 - \(\dfrac{8}{15}\)
3 \(\times\) y = \(\dfrac{22}{15}\)
y = \(\dfrac{22}{15}\) : 3
y = \(\dfrac{22}{45}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
`Answer:`
a. \(x+12=3\Leftrightarrow x=3-12\Leftrightarrow x=-9\)
b. \(2x-15=21\Leftrightarrow2x=21+15\Leftrightarrow2x=36\Leftrightarrow x=36:2\Leftrightarrow x=18\)
c. \(13-3x=4\Leftrightarrow-3x=4-13\Leftrightarrow-3x=-9\Leftrightarrow x=-9:-3\Leftrightarrow x=3\)
d. \(2\left(x-2\right)+4=12\Leftrightarrow2x-4+4=12\Leftrightarrow2x=12\Leftrightarrow x=12:2\Leftrightarrow x=6\)
e. \(15-3\left(x-2\right)=21\Leftrightarrow15-3x+6=21\Leftrightarrow-3x=21-15-6\Leftrightarrow-3x=0\Leftrightarrow x=0\)
g. \(25+4\left(3-x\right)=1\Leftrightarrow25+12-4x=1\Leftrightarrow37-4x=1\Leftrightarrow-4x=-36\Leftrightarrow x=9\)
h. \(3x+12=2x-4\Leftrightarrow3x-2x=-4-12\Leftrightarrow x=-16\)
i. \(14-3x=\left(-x\right)+4\Leftrightarrow-3x+x=4-14\Leftrightarrow-2x=10\Leftrightarrow x=5\)
k. \(2\left(x-2\right)+7=x-25\Leftrightarrow2x-4+7=x-25\Leftrightarrow2x-x=-25-3\Leftrightarrow x=-28\)
![](https://rs.olm.vn/images/avt/0.png?1311)
bài 1:
a) 1/3x=-5/3
x=-5
b) x+12/5=37/15
x=1/15
c) x-1/7=-36/7
x=-5
d) 3x-1/2=0
3x=1/2
x=1/6
e) 2/5+x=1/4
x=-3/20
![](https://rs.olm.vn/images/avt/0.png?1311)
1) -12 . 12 = x .48
-144 = x . 48
-144 : 48 = x
-3 = x
2) -17 - 4 ( x - 2 ) = -15 - 6 ( x + 1 )
-17 - 4x + 8 = -15 - 6x - 6
-4x + 6x = - 15 - 6 + 17 - 8
2x = -10
x = -5
3) 4x - 7 = 3x - 15
4x - 3x = -15 + 7
x = -8
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x/12 = -1/24 - 1/8
x/12 = -1/6
x/12 = 2/12
x = 2 X 12 : 12
Vậy x = 2
b) 2/3 . x - 1/2 .x = 5/4
x.(2/3-1/2) = 5/4
x.1/6 = 5/4
x = 5/4 :1/6
Vậy x = 15/2
![](https://rs.olm.vn/images/avt/0.png?1311)
( 2 x y + 2/15 ) x 3 = 4/5
( 2 x y + 2/15 ) = 4/5 : 3
( 2 x y + 2/15 ) = 4/15
2 x y = 4/15 - 2/15
2 x y = 2/15
y = 2/15 :2
y = 1/15
(2 x y + 2/15) x 3 = 4/5
2 x y + 2/15) = 4/5 : 3
2 x y + 2/15 = 4/15
2 x y = 4/15 - 2/15
2 x y = 2/15
y = 2/15 : 2
y = 1/15
7/9 x (2 - 1/3 x y) = 14/15
(2 - 1/3 x y) = 14/15 : 7/9
(2 - 1/3 x y) = 6/5
2 - y = 6/5 x 1/3
2 - y = 2/5
y = 2/5 + 2
y = 12/5
4/21 + 5 x y - 8/7 = 1/3
4/21 + 5 x y = 1/3 + 8/7
4/21 + 5 x y = 31/21
5 x y = 31/21 - 4/21
5 x y = 9/7
y = 9/7 : 5
y = 9/35
7/12 x y - 3/12 x y = 5
y x (7/12 - 3/12) = 5
y x 1/3 = 5
y = 5 : 1/3
y = 15
\(\frac{2}{3}-\frac{1}{2}x=\frac{15}{12}\)
\(\Leftrightarrow\frac{1}{2}x=\frac{2}{3}-\frac{15}{12}\)
\(\Leftrightarrow\frac{1}{2}x=\frac{8}{12}-\frac{15}{12}\)
\(\Leftrightarrow\frac{1}{2}x=\frac{-7}{12}\)
\(\Leftrightarrow x=\frac{-7}{12}\div\frac{1}{2}\)
\(\Leftrightarrow x=\frac{-7}{12}\times\frac{2}{1}\)
\(\Leftrightarrow x=\frac{-14}{12}=\frac{-7}{6}\)